Hadis-hadis Dakwah dalam Bidang Pendidikan - Ridwan, Ridwan; Abustani Ilyas; Muh. Tasbih (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2024)
This research aims to identify and analyse relevant hadiths in the context of education in Islam. This study employs a qualitative descriptive approach, focusing on literature review and textual analysis of selected hadiths. The analysis reveals that the hadiths of the Prophet Muhammad (PBUH) hold a significant position in shaping the concepts and practices of education in Islam. Key findings include the importance of etiquette in eating and drinking as part of character education, the obligation of seeking knowledge as a religious foundation for every Muslim, and the significance of knowledge as an invaluable legacy from the Prophets. Additionally, the research highlights the importance of knowledge for both worldly success and the Hereafter, along with Allah's promise to facilitate the path to Paradise for seekers of knowledge. The implications of this research contribute to deepening the understanding of educational values in Islam and provide practical recommendations for education practitioners and parents in guiding the younger generation. It is hoped that the findings of this research will serve as a basis for developing educational curricula grounded in Islamic values and enhancing the understanding and implementation of Islamic teachings in modern educational contexts.